Scheduling in Bag-of-Task grids: the PAUA case - Cirne, W.; Brasileiro, F.; Costa, L.; Paranhos, D.; Santos-Neto, E.; Andrade, N.; Rose, C. De; Ferreto, T.; Mowbray, M.; Scheer, R.; Jornada, J. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
In this paper we discuss the difficulties involved in the scheduling of applications on computational grids. We highlight two main sources of difficulties: 1) the size of the grid rules out the possibility of using a centralized scheduler; 2) since resources are managed by different parties, the scheduler must consider several different policies. Thus, we argue that scheduling applications on a grid require the orchestration of several schedulers, with possibly conflicting goals. We discuss how we have addressed this issue in the context of PAUA, a grid for Bag-of-Tasks applications (i.e. parallel applications whose tasks are independent) that we are currently deploying throughout Brazil.